Moderators of Implicit-Explicit Exercise Cognition Concordance - Berry, Tanya R; Rodgers, Wendy M; Markland, David; Hall, Craig R (Journal of sport & exercise psychology, 2016)
Investigating implicit-explicit concordance can aid in understanding underlying mechanisms and possible intervention effects. This research examined the concordance between implicit associations of exercise with health or appearance and related explicit motives. Variables considered as possible moderators were behavioral regulations, explicit attitudes, and social desirability. Participants (N = 454) completed measures of implicit associations of exercise with health and appearance and questionnaire measures of health and appearance motives, attitudes, social desirability, and behavioral regulations. Attitudes significantly moderated the relationship between implicit associations of exercise with health and health motives. Identified regulations significantly moderated implicit-explicit concordance with respect to associations with appearance. These results suggest that implicit and explicit exercise-related cognitions are not necessarily independent and their relationship to each other may be moderated by attitudes or some forms of behavioral regulation. Future research that takes a dual-processing approach to exercise behavior should consider potential theoretical moderators of concordance.